EFFECT OF PENDING IN PENDING IN PARTICULAR PAD A PAJAH GEM OF DOUBLE CUT - Didik Nurhadiyanto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The purpose of this study, are (1) to compare the wear of a single cutter with a double cutter with the use of different cooler viscosity, (2) to determine the effect of cooller viscosity to cutter wear, and (3) find a suitable viscosity, cooling to reduce cutter wear. The workpiece material is VCN 150 ø 1.75 inches with a length of cut is 200 mm. Variables that are altered depth of cut. The depth of cut is defined initial minus end diameter divided by two. The depth of cut for a double edged pieces with a single piece. Cutter wear modifications largest taken from each eye piece for comparison with a single cutter. Research steps undertaken were as follows: wear to keep records of each viscosity cooling, ie 14.5 poise, poise 24.8, 35.6 poise, and poise while the depth of 49.2 pieces 0.5; 1; 1.5; and 2 mm. Each observation performed 3 times and subsequently taken average. Comparing the wear obtained in cutting using single and double cutting. The results of this study are as follows: (1) a reduction in the cutter wear double edged pieces of 18.64% compared with a single cutter with variable thickness and depth of cut cooling. (2) work without cooling wear very large, so that liquid cooling is needed in the process of cutting the workpiece, (3) become less viscous cooling is used, a reduction in wear and tear on the range. Wear and tear occurs in the thickness of the smallest 14.5 poise.Keywords: cooling, wear, and the depth of cut